PERLINDUNGAN BAGI PEKERJA YANG MENGALAMI SAKIT SETELAH BERAKHIRNYA HUBUNGAN KERJA - Happy Sukerti, Ni Nyoman; Lamury Hadjon, Edward Thomas (Kertha Semaya : Journal Ilmu Hukum, 2014)
Law number 13 of 2013 concerning Employment requires the protection and safety measures of the worker to be included. However, it is often found that during the termination of working contract, diseases caused by employment of an employee during the working contract emerged.This paper uses normative legal research and statutory approach with the aim of knowing the arrangement of working accident and protection of workers who became ill after the end of employment. The conclusion of this paper are arrange in article 86 of Employment Act and the worker who becoming ill after the end of work relation still in industrialist’s responsible.
Keywords: Labor relation, Working accident